Short-term results of a phase II study of preoperative docetaxel/cisplatin/S-1 therapy for locally advanced gastric cancer. (3rd December 2020) - Tsuchida, Kazuhito; Sato, Tsutomu; Aoyama, Toru; Atsumi, Yosuke; Kano, Kazuki; Maezawa, Yukio; Kazama, Keisuke; Numata, Masakatsu; Yamada, Takanobu; Tamagawa, Hiroshi; Murakami, Hitoshi; Oshima, Takashi; et al.
Abstract: Background: A multi-institutional phase II study was conducted to evaluate the efficacy and safety of preoperative docetaxel, cisplatin and S-1 therapy in marginally resectable advanced gastric cancer. Methods: Patients with macroscopic type 4, large macroscopic type 3 and bulky lymph node metastasis received two cycles of preoperative docetaxel, cisplatin and S-1 therapy (docetaxel 40 mg/m 2 and cisplatin 60 mg/m 2 on day 1, and S-1 80 mg/m 2 for 14 days, every 4 weeks). The primary endpoint was the pathological response rate, with an expected value of 65%. Results: Thirty-one patients were enrolled in this study. The pathological response rate was 54.8%, and it was higher than the threshold value but lower than the expected rate. The R0 resection rate was 93.5%. The frequencies of grade 3–4 toxicities during docetaxel, cisplatin and S-1 therapy were 41.9% for neutropenia, 6.5% for febrile neutropenia and 32.3% for nausea/vomiting. Grade 2 and 3 surgical morbidities occurred in 23.3 and 6.7% of the patients, respectively. Conclusions: Preoperative docetaxel, cisplatin and S-1 therapy was feasible in terms of chemotherapy-related toxicities and surgical morbidity, but the effect did not achieve the expected value. The association between the pathological response rate and survival will be evaluated in the final analysis of this clinical trial. Abstract : A phase II study of preoperative docetaxel/cisplatin/S-1 therapy for locally advanced gastric cancer was feasible, but the pathological response rate did not achieve the expected value.